Reduction of pollutant concentrations in the plant systems with the inert filter bed. Part I: biological absorbtion of nitrogen and phosphorus in nitrophytes in micro - cultivations fertilized with domestic wastewater = Redukcja stężeń zanieczyszczeń w roślinnych systemach ze złożem inertnym. Część pierwsza: absorpcja biologiczna azotu i fosforu w nitrofitach z mikroupraw nawożonych ściekami bytowymi - Dąbek, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication presents the experiment conducted on the nitrophyte plants of the species Polygonum persicaria L. and Epilobium parviflorum Schr., in the micro- cultivation with the inert filter bed filled in with an artificial aggregate, keramzite. The plants were fertilized with domestic wastewater separated in a well settling tank with the Čoanda effect separator.
Keywords: absorpcja biologiczna; migracja; keramzyt; nitrofity; ścieki bytowe; absorption; migration; keramzite; nitrophytes; lithospheric clarke; separated wastewater